Health & wellbeing in offices - A study of literature on the Nordic perspective. (August 2019) - Forooraghi, Melina; Wallbaum, Holger; Ryd, Nina
Abstract: Aim : This review aims to explore the relation between the physical office environment and employee health as found in the Nordic literature.Background : The Nordic countries have a worldwide fame for their high living and working standards. Nevertheless, they have also been facing global challenges related to demographic changes, aging population, and a rise in long term conditions which require a creative way of thinking, and innovative approaches in the ways we deliver buildings and the built environment. The built environment is a health determinant and a resource for health and wellbeing of building users. In office sector, however, there is little known regarding the design implications of the physical environment for health outcomes. A review of the literature on the current state of the art in the Nordic context could offer an opportunity to rethink office design and support dialogue on how better design can improve employee health outcomes.Methods : An explorative document analysis of recent literature on workplace environment in the Nordic context was carried out.Results : Three main gaps in the literature were identified, including (1) limited understanding of health, (2) unrecognised role of the physical work environment and design professions in relation to health, and (3) diverse research orientations. The combination of results suggests the paucity of the studies relating the physical office environment to positive health approaches.Conclusions : This review highlights the need for more quantitative and qualitative methods to give relevant knowledge for complex questions regarding the physical office environment and health outcomes of employees. Future research should enable dialogue and collaboration between different actors such as managers, human resources, occupational health professionals and designers, which can benefit the users of office building.